Intranasal immunization with influenza VLPs incorporating membrane-anchored flagellin induces strong heterosubtypic protection. - Bao-Zhong Wang; Rui Xu; Fu-Shi Quan; Sang-Moo Kang; Li Wang; Richard W Compans (PLoS ONE)
We demonstrated previously that the incorporation of a membrane-anchored form of flagellin into influenza virus-like particles (VLPs) improved the immunogenicity of VLPs significantly, inducing partially protective heterosubtypic immunity by intramuscular immunization. Because the efficacy of mucosal vaccination is highly dependent on an adjuvant, and is particularly effective for preventing mucosal infections such as influenza, we determined whether the membrane-anchored flagellin is an efficient adjuvant for VLP vaccines by a mucosal immunization route. We compared the adjuvant effect of membrane-anchored and soluble flagellins for immunization with influenza A/PR8 (H1N1) VLPs by the intranasal route in a mouse model. The results demonstrate that membrane-anchored flagellin is an effective adjuvant for intranasal (IN) immunization, inducing enhanced systemic and mucosal antibody responses. High cellular responses were also observed as shown by cytokine production in splenocyte cultures when stimulated with viral antigens. All mice immunized with flagellin-containing VLPs survived challenge with a high lethal dose of homologous virus as well as a high dose heterosubtypic virus challenge (40 LD(50) of A/Philippines/82, H3N2). In contrast, no protection was observed with a standard HA/M1 VLP group upon heterosubtypic challenge. Soluble flagellin exhibited a moderate adjuvant effect when co-administered with VLPs by the mucosal route, as indicated by enhanced systemic and mucosal responses and partial heterosubtypic protection. The membrane-anchored form of flagellin incorporated together with antigen into influenza VLPs is effective as an adjuvant by the mucosal route and unlike standard VLPs, immunization with such chimeric VLPs elicits protective immunity to challenge with a distantly related influenza A virus.